Analisis Sistem Akuntansi Pendapatan Dalam Penetapan Jumlah Gaji Pegawai Pada Rs Surya Medika Gresik - Muhammad Habibie Al Hamzah (CV. Ulil Albab Corp, 2022)
The purpose of this research discussion is to find out whether the accounting system of solar medics income RS Surya Medika whether it can support the accuracy of the total salary of employees. Themethod inthis research is descriptive research with a qualitative approach. The data analysis technique used was survey, interview and documentation. The result obtained by researchers namely stated that RS Surya Medika has an adequate accounting information system to support the accuracy of the total salary of the employees in terms of the income system used by RS Surya Medika. But there are still some weaknesses, namely the concurrent assigment of the financial departement, the documents used are not complete such as accounting records that are used only general journals.based on that suggestion given to RS Surya Medika is the need for the application on maximum payroll procedures, it is necessary to separate the task beetween the personnel and the financial department. This is to facilitate the distribution of tasks facilitate supervision and the need for an increase in the quality of human resources so that it can support the success of the solar RS Sakit Surya Medika.